2012
DOI: 10.1016/j.joca.2012.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNAs during chondrogenesis of human adipose-derived stem cells

Abstract: In this study we have identified a group of miRNAs and their target genes, which may play important roles in regulating chondrogenic differentiation of hADSCs. Our results provide the basis for further investigation into the molecular mechanism of chondrogenesis in hADSCs and their differentiation for cartilage engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 56 publications
3
77
0
Order By: Relevance
“…We found that miR-455-3p, miR-193b, miR-199a-3p/hsa-miR-199b-3p, miR-210, miR-381, miR-92a, miR-320c, and miR-136 were up-regulated [1]. In this work, we further studied the expression and regulation of one representative miRNA known to be increased in chondrogenesis, miR-455-3p [1,5]. We demonstrated a critical role for miR-455-3p as an activator in early chondrogenesis.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…We found that miR-455-3p, miR-193b, miR-199a-3p/hsa-miR-199b-3p, miR-210, miR-381, miR-92a, miR-320c, and miR-136 were up-regulated [1]. In this work, we further studied the expression and regulation of one representative miRNA known to be increased in chondrogenesis, miR-455-3p [1,5]. We demonstrated a critical role for miR-455-3p as an activator in early chondrogenesis.…”
Section: Discussionmentioning
confidence: 82%
“…To explore the specific involvement of miRNAs in the chondrogenesis of MSCs, we previously used the miRNA microarray technique to profile miRNA expression and screen miRNAs with significant differences in expression before and after chondrogenic induction. We found that miR-455-3p, miR-193b, miR-199a-3p/hsa-miR-199b-3p, miR-210, miR-381, miR-92a, miR-320c, and miR-136 were up-regulated [1]. In this work, we further studied the expression and regulation of one representative miRNA known to be increased in chondrogenesis, miR-455-3p [1,5].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations